The Conceptual Guidelines for Integration of Croatia into the European Air Traffic Management System - Steiner, Sanja; Radačić, Željko; Mikula, Miroslav (Promet - Traffic&Transportation, 2012)
Full implementation of the final phase of EATCHIP isplanned for the beginning of the 21’ century. It will re-define theEuropean system of air traffic regulation and control. The integrationof a great number of ATC systems into a unique operativenetwork is supported by the technical modernisation andstandardisation of the communication, navigation and radardevices. Integration of Croatia into the European air trafficcontrol system assumes its active participation in the cun·entprojects, implementation of relevant technical standards andthe national air traffic development strategy within the contextof Euro-atlantic integration.